Republic Of Poland : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that the annual growth in Poland in 2004 reached 5 1\2 percent, with a surge in growth in the run-up to European Union accession dissipating in the second half of 2004. Both domestic and net external demand contributed to the slowdown. Consumption and inventory accumulation had supported output growth as contribution of net external demand diminished, but by mid-2004, these sources of demand growth slackened. The recovery has started to produce jobs, but the employment rate remains low owing to structural rigidities and demographic pressures.